2006
DOI: 10.1007/11935230_17
|View full text |Cite
|
Sign up to set email alerts
|

Trading One-Wayness Against Chosen-Ciphertext Security in Factoring-Based Encryption

Abstract: Abstract. We revisit a long-lived folklore impossibility result for factoring-based encryption and properly establish that reaching maximally secure one-wayness (i.e. equivalent to factoring) and resisting chosenciphertext attacks (CCA) are incompatible goals for single-key cryptosystems. We pinpoint two tradeoffs between security notions in the standard model that have always remained unnoticed in the Random Oracle (RO) model. These imply that simple RO-model schemes such as Rabin/RW-SAEP[+]/OAEP [+][+], EPOC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 17 publications
2
46
0
Order By: Relevance
“…Note that, at this point, we are still in a setting with an all-powerful oracle Σ and the non-interactive problem may indeed be easy relative to this oracle, without contradicting the presumed hardness in the standard model. Now we apply meta-reduction techniques, as put forward for example in [7,9,14,28], to remove the oracle Σ from the scenario. Given R we show how to build a meta-reduction M (a "reduction for the reduction") to derive an efficient solver for the problem, but now without any reference to the magic adversary and Σ (right part of Figure 1).…”
Section: The Idea Behind Our Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Note that, at this point, we are still in a setting with an all-powerful oracle Σ and the non-interactive problem may indeed be easy relative to this oracle, without contradicting the presumed hardness in the standard model. Now we apply meta-reduction techniques, as put forward for example in [7,9,14,28], to remove the oracle Σ from the scenario. Given R we show how to build a meta-reduction M (a "reduction for the reduction") to derive an efficient solver for the problem, but now without any reference to the magic adversary and Σ (right part of Figure 1).…”
Section: The Idea Behind Our Resultsmentioning
confidence: 99%
“…The other approach uses meta-reductions [4,7,8,9,14,28] and usually treats the adversary as a black box. In our case, we show that no black-box reduction to arbitrary (non-interactive) cryptographic problems can exist.…”
Section: The Essence Of Our Meta-reduction and Impossibility Of Randomentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, in the realm of factoring/RSA-based CCA encryption, Paillier and Villar [30] and Brown et al [6], showed uninstantiability results analogous to already-mentioned RSA signature result of Paillier [28].…”
Section: Other Related Workmentioning
confidence: 73%